Radicalisation Tinted by Nationalism or How to Turn a Counterrevolutionary Into a Reactionary: Ingo Schulze's Die rechtschaffenen Mörder (The Righteous Murderers) (2020) - Gortych, Dominika Anna (Porównania, 2021)
The article attempts to integrate the British Brexit experience into the pan-European context of expanding populist and nationalist movements and the radicalization of modern societies caused by crises such as socio-political breakthroughs. Although this article deals primarily with the German history of the division of the state and the complex process of its reunification, it also analyses the subject matter within the framework of culturally-oriented literary studies, which allows us to identify some universal features and categories describing such phenomena as, for instance, the sense of individual deprivation, loss of orientation in reality affected by crises, creating a negative image of strangers due to the fear of losing one’s own identity, and susceptibility to populism.